Integrated aircraft and research vessel observational studies of aerosols and clouds in summer over the western North Pacific - Makoto Koike; Yoshimi Kawai; Kouji Adachi; Hidenori Aiki; Yugo Kanaya; Hideaki Kawai; Kazuyuki Kita; Fumiyoshi Kondo; Tsuyoshi Koshiro; Hitoshi Matsui; Takuma Miyakawa; Ayumu Miyamoto; et al. (Progress in Earth and Planetary Science)
Abstract An integrated observational study of aerosols and clouds was carried out in summer 2022 over the western North Pacific (off the eastern coast of Hokkaido, Japan) using both an aircraft and a research vessel for the first time in this area. The aim of this experiment was to characterize the physical and chemical properties of aerosols and to evaluate the contributions of anthropogenic and natural emissions to cloud condensation nuclei (CCN) and ice-nucleating particle (INP) concentrations. The experiment also aims to examine the vertical structure of low-level clouds, which have high radiative effects, over this region. Here, we present an overview of the experiment and some preliminary results. Onboard the research vessel, suspended particulate matter in seawater was sampled, and the size distributions of dominant particle types (e.g., diatom fragments and organic matter) were determined. By analyzing atmospheric aerosols sampled from aircraft, we derived the number size distributions of dust-like particles in the air far from source regions. The aerosol size distributions, as measured from both the vessel and aircraft, suggested that most of the aerosols that could act as CCN were of anthropogenic origin: The upper-bound estimate of the sea spray aerosol (SSA) contribution to the CCN concentration at altitudes below 1200 m was 23%. Numerical model simulations generally reproduced the observed aerosol number concentrations. The simulations supported the inference from the observation that most CCN over the study area were of anthropogenic origin. Using this model, SSA emissions were estimated to account for 9% of the cloud radiative effect. Cloud observations from aircraft revealed that low-level clouds tended to have an adiabatic vertical structure under cold air advection, whereas under warm air advection, they occasionally had a layered structure. Such diverse vertical structures of low-level clouds are not generally seen in the subtropics. The integrated observations carried out in this study provided a basic picture of aerosols and clouds over the study area in summer. Further research is needed to elucidate the roles of aerosols in cloud formation and the radiation budget under various meteorological conditions within the framework of atmosphere–ocean interactions.